A blog as an innovative tool in literature courses: a collaborative learning experience - Saravia Vargas, Juan Carlos (Escuela de Lenguas Modernas, Universidad de Costa Rica, 2010)
The academic essay has been the technique of choice of most literature professors to assess the progress of their students. Yet, technology provides new tools today that might benefit the process of teaching/learning literary elements. One of such instruments is the blog, a free online sharing space that instructors can use to upload material and allow their students to share reactions, impressions, questions, and points of analysis.